POSISI PERGURUAN TINGGI AGAMA ISLAM DALAM PENGEMBANGAN PEMIKIRAN HUKUM ISLAM - Herfin Fahri (Al Hikmah: Jurnal Studi Keislaman, 2017)
Development of Islamic Legal Thought “Islamic Law (Shari'ah)” is one important field of study, perhaps the most important fact in the scientific tradition of Islam, this is not because the tradition of jurisprudence among Indonesian Muslims, but because Islamic Law (Shari'ah) is the main reference for Muslims in behave. The College of Islam in Indonesia to position and portray himself in the changes and challenges of the present and the future. Changes that occur globally Essential globalization of the economy and the conflict of civilizations, the rapid development of science “knowledge” and technology and the challenges facing humanity in connection with the crisis of spiritual values in the atmosphere of the people who have been eroding Islamic values and morals.The existence of the Islamic university today is how the Islamic university in Indonesia to position and portray himself in the changes and challenges of the present and the future.